Seasonal somatic reserves of a northern ungulate influenced by reproduction and a fire-mediated landscape - Thompson, Daniel P.; Fowler, Nicholas L.; Crouse, John A.; McDonough, Thomas J.; Badajos, Oriana H.; Spathelf, Miles O.; Watts, Dominique E.; Rodman, Susanne U. (Frontiers in Ecology and Evolution, 2024)
Wildlife contend with seasonal fluctuations in resource availability and have adapted survival and reproductive strategies to overcome resource limitations. Many northern ungulates are adapted to a dynamic nutritional landscape and rely on somatic reserves accumulated during the short growing season. Moose (Alces alces) populations in the boreal forest respond to variation in their nutritional landscapes that quickly change after wildland fires. We tested associations between somatic energy reserves of female moose and a suite of factors relevant to energy demands and nutrient availability after landscape scale wildland fires on the Kenai Peninsula, Alaska. From 2015–2022, we immobilized 97 individual, adult moose (n=163 early winter; n=98 late winter) and collected over 223,000 GPS locations. We evaluated if somatic energy reserves of cow moose were influenced by endogenous or exogenous energy demands, or access to moose forage to accumulate energy reserves. Cows that gave birth and lost their neonate(s) early in the summer had more early winter body fat (14.39% ± 0.24SE) compared with cows that gave birth and the neonate survived to 4-months-old (10.59% ± 0.34SE). Body fat measured in early winter was positively correlated with home ranges of cows during summer with a higher percent cover of aspen forage. Late winter body fat of cow moose was negatively correlated with home ranges with higher percent cover of aspen forage, but positively correlated with home ranges with higher percent cover of willows and shoulder season forages. Our results highlight that a suite of plant species and seral states is needed across the landscape for moose to accumulate and moderate the loss of somatic energy reserves over the year. Furthermore, our results emphasize the importance of shoulder season forages for moose when snow depth is low. Managing the nutritional landscape of the boreal forest through interagency wildland fire management could create a mosaic of seral states that enhances moose forage, while reducing wildland fire hazards along the wildland urban interface and providing ecosystem services.